2018
DOI: 10.1159/000493670
|View full text |Cite
|
Sign up to set email alerts
|

Deletion and Functional Analysis of Hepatitis B Virus X Protein: Evidence for an Effect on Cell Cycle Regulators

Abstract: Background/Aims: The hepatitis B virus X protein (HBx) is a viral trans-activator that plays a crucial role in pathogenesis of hepatocellular carcinoma (HCC) via an unknown mechanism. The role of HBx in modulating cell proliferation and programmed cell death is replete with controversies. Thus, the goal of this study was to elucidate the effect of HBx and its deletion mutants on cell cycle progression in human hepatoma cells. Methods: Huh7 cells transfected with either full-length or truncated HBx were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Negative-expression of Fas might impede the sustainable anti-viral response of death ligand stimulus-specific apoptotic pathway. In contrast, as a target gene relevant to execution and completion of apoptosis, the overexpressed CDKN1A triggered by HBx-induced HDAC4 inhibition was concordant with the earlier research that HBx can relieve a block on CDKN1A expression and prolong G1→S transition in human hepatoma cells [156,157]. Even though p21, the protein encoded by CDKN1A, is treated as a cyclin-dependent kinase inhibitor capable of inhibiting all cyclin/CDK complexes, it often promotes the assembly of type-D cyclins with CDK4 and CDK6 and arrests cell cycle progression in the G1 phase [156,158], which not only protects cells against apoptosis but also enhances the chance of tumorigenesis.…”
Section: Apoptosis In Hbv Infectionsupporting
confidence: 89%
“…Negative-expression of Fas might impede the sustainable anti-viral response of death ligand stimulus-specific apoptotic pathway. In contrast, as a target gene relevant to execution and completion of apoptosis, the overexpressed CDKN1A triggered by HBx-induced HDAC4 inhibition was concordant with the earlier research that HBx can relieve a block on CDKN1A expression and prolong G1→S transition in human hepatoma cells [156,157]. Even though p21, the protein encoded by CDKN1A, is treated as a cyclin-dependent kinase inhibitor capable of inhibiting all cyclin/CDK complexes, it often promotes the assembly of type-D cyclins with CDK4 and CDK6 and arrests cell cycle progression in the G1 phase [156,158], which not only protects cells against apoptosis but also enhances the chance of tumorigenesis.…”
Section: Apoptosis In Hbv Infectionsupporting
confidence: 89%
“…Primers targeting the 3′ end of all transcripts (3′T) will amplify both cccDNA- and iDNA-derived RNAs, whereas those targeting the repeat region (RR), which is absent in the majority of id-RNAs, will only amplify cccDNA-derived RNAs [ 14 , 29 ] ( Figure 3 A). The 3′T primers will amplify pC/pg splice variants [ 11 ] and two of the three known HBx truncated transcripts [ 30 ]. Both 3′T and RR primer pairs target regions conserved among diverse genotypes and showed a linear amplification of HBV genotype D over a 5-log range ( Supplementary Figure S4A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…During the past few years, there has been a shift towards the study of truncated HBx proteins, whose functional mode presents differences as opposed to the wild type 50 . Transfection of human hepatoma cell line Huh7 with full‐length or truncated HBx was tested in a series of cell cycle‐related proteins and the results showed an enhanced modulation in both cases 51 . In another study, the effect of HBx on G1/S checkpoint control, based upon the status of p53, was investigated in NIH3T3 cells and it was shown that when p53 was present, transcription of p21waf1/cip1 was activated in a dose‐dependent manner 52…”
Section: Hbv‐related Hcc and Cellular Senescencementioning
confidence: 99%